Mapping the co-benefits of climate change action to issues of public concern in the UK: a narrative review. Issue 9 (September 2020) - Jennings, Neil; Fecht, Daniela; De Matteis, Sara
Summary: To avoid a 1·5°C rise in global temperatures above preindustrial levels, the next phase of reductions in greenhouse gas emissions will need to be comparatively rapid. Linking the co-benefits of climate action to wider issues that the public are concerned about can help decision makers to prioritise decarbonisation options that increase the chance of public support for such changes, while ensuring that a just transition is delivered. We identified key issues of concern to the UK public by use of Ipsos MORI public opinion data from 2007 to 2020 and used these data to guide a narrative review of academic and grey literature on the co-benefits of climate change action for the UK. Correspondence with civil servants, third sector organisations, and relevant academics allowed us to identify omissions and to ensure policy relevance of the recommendations. This evidence-based Review of the various co-benefits of climate change action for the UK identifies four main areas: health and the National Health Service; security; economy and unemployment; and poverty, housing, and inequality. Associated trade-offs are also discussed. City-level and regional-level governments are particularly well placed to incorporate co-benefits into their decision making because it is at this scale that co-benefits most clearly manifest, and where interventions can have the most immediate effects.